Help me with this question please
1 answer:
First find the equation of the line:
y - b = m (X - a)
y - 5 = 2/3 (X + 2)
3y - 15 = 2 (X + 2)
3y - 15 = 2x + 4
3y = 2x + 19
Then sub the y-value of A into the equation to find X.
y = 3
3(3) = 2x + 19
9 = 2x + 19
2x = 10
X = 5
And sub the X-value of B into the equation to find y.
X = -2
3y = 2(-2) + 19
3y = -4 + 19
3y = 15
y = 5
You might be interested in
15 - 2(- 13s + 3) = 9s - 9 + 16s
15 + 26s - 6 = 25s - 9
9 + 26s = 25s - 9
26s - 25s = -9 - 9
s = - 18
Answer:
can you take a better pic so i can help
Step-by-step explanation:
Its B just took the test the answer is B